Understanding the causes of missed miscarriage during the first trimester - Niaz, Mamoona; Nadeem, Sawera; Khan, Malaika (Journal of the Pakistan Medical Association, 2026)
Dear Editor, Miscarriage is a spontaneous pregnancy loss before fetal viability.(¹) Missed miscarriage, a form of pregnancy loss which occurs when a foetus fails to develop and stays in the uterus, and the mother usually doesn’t have specific symptoms. There is no doubt that it is a common complication of pregnancy amid 12 weeks of gestation and leaves a major setback on parents’ lives. A recent study has demonstrated that the incidence of this asymptomatic early pregnancy loss is found to be about 38% among all EPLs in a nationwide registry study in Finland. (²) These results are a reason for concern, especially in developing countries like Pakistan, where there is a lack of awareness about missed miscarriage, its causes, and approaches to it. Patients who suffer from missed miscarriage include vast causes like abnormal fetal karyotype, particularly trisomy, which can be either trisomy 15,16,21 or 22. (³) Maternal risk factors such as maternal age, in which mothers below 20 years of age and above 30 years of age is more liable to this. Other than that, an estimated 5% to 30% of women with a history of EPL have an underlying uterine anatomic anomaly. (²) To add on factors like intake of alcohol or NSAIDs during pregnancy, endocrine problems like type 1 or 2 DM, thyroid disease, and PCOS contribute to missed miscarriage. It is worth mentioning that the diagnosis of missed miscarriage results in emotional distress in parents’ lives and is often associated with other health problems including mental health as well. Recent studies have shown an increased incidence of type 2 diabetes, hypercholesterolemia, and hypertension in women with a past medical history of miscarriage. (²)There was no article found tending this issue in Pakistan after a comprehensive online literature search on PubMed, which further spots the lack of attention given to this commonly occurring complication during reproductive age. Subsequently, it is the need of hour to conduct studies with respect to missed miscarriage during the first trimester as individuals in Pakistan are not apprised about its aspects and thus suffer too. Healthcare institutions should engage clinicians to gather data on missed miscarriages for further interpretation and analysis. In addition, this way people will get to know about it and its significance, especially given that its incidence is increasing, affecting patients’ health. So, healthcare professionals must take proactive steps to address this and enhance the quality of life of women during their reproductive years.